2015
DOI: 10.1177/1356336x15594548
|View full text |Cite
|
Sign up to set email alerts
|

Can physical education and physical activity outcomes be developed simultaneously using a game-centered approach?

Abstract: The primary objective of this study was to evaluate the efficacy of a pilot intervention using a gamecentered approach for improvement of physical activity (PA) and physical education (PE) outcomes simultaneously, and if this had an impact on enjoyment of PE. A group-randomized controlled trial with a 7-week wait-list control group was conducted in one primary school in the Hunter Region, NSW, Australia. Participants (n ¼ 107 students; mean age ¼ 10.7 years, SD 0.87) were randomized by class group into the Pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
62
3
7

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(78 citation statements)
references
References 73 publications
6
62
3
7
Order By: Relevance
“…However, the investigation showed that students were more likely to attain the 50% MVPA level in game-focused instruction than skillfocused instruction. This mirrors previous findings that invasion game-type lessons yielded higher amounts of MVPA for students (Fairclough & Stratton, 2005 and studies that have argued that GCAs such as the TGM are more likely to create a context for higher MVPA levels when compared to direct instruction games lessons where the emphasis is predominantly technical skill instruction (i.e., Harvey et al, 2015;Miller et al, 2016;Smith et al, 2015). For the middle school students, in the second part of game play MVPA was significantly higher than both the first part of game play, and skill practice.…”
Section: Jpes ®supporting
confidence: 83%
See 1 more Smart Citation
“…However, the investigation showed that students were more likely to attain the 50% MVPA level in game-focused instruction than skillfocused instruction. This mirrors previous findings that invasion game-type lessons yielded higher amounts of MVPA for students (Fairclough & Stratton, 2005 and studies that have argued that GCAs such as the TGM are more likely to create a context for higher MVPA levels when compared to direct instruction games lessons where the emphasis is predominantly technical skill instruction (i.e., Harvey et al, 2015;Miller et al, 2016;Smith et al, 2015). For the middle school students, in the second part of game play MVPA was significantly higher than both the first part of game play, and skill practice.…”
Section: Jpes ®supporting
confidence: 83%
“…However, research shows that many physical educators fail to meet this recommendation with their students (Hollis, Williams, Sutherland et al, 2015). However, some recent research suggests that the lack of evidence demonstrating teachers can meet this recommendation may be about the model of teaching that is being utilized by the physical educator (i.e., Harvey et al, 2016a;Miller et al, 2016;Smith et al, 2015;Van Acker et al, 2010). For example, Smith et al, (2015) showed that a physical education teacher who utilized the Tactical Games Model could reach meet this 50% MVPA recommendation when compared to a teacher who used a more traditional, direct instruction approach to teaching games.…”
Section: Introductionmentioning
confidence: 99%
“…Others also emphasize that teachers who exhibit a deep understanding of game-centered pedagogy are capable of balancing the teaching of skills/tactics in a game play context (Dudley & Baxter, 2009;Dudley & Baxter, 2013). Simultaneous development of FMS and tactical skill has been demonstrated using such an approach (Miller, Christensen, Eather, Gray, et al, 2015;. This implies that teachers and researchers need to (and can) move from seeing 'skills teaching' and 'tactical instruction' as distinct elements of PE to a position where the interrelationship existing between skills and tactics is paramount (Dudley & Baxter, 2009).…”
Section: Critique 4: That a Focus On Fms Ignores A Constraints-based mentioning
confidence: 99%
“…The implementation of game centred teaching ,through teacher professional development, in a NSW regional primary school demonstrated improvements in skill, physical activity, decision making and perception (Miller et al, 2015).…”
Section: Pedagogical Possibilities and Game Centred Teaching (Gct)mentioning
confidence: 99%